Plants causing poisoning outbreaks of livestock in South America: A review - Franklin Riet-Correa; Mizael Machado; Juan F. Micheloud (Toxicon: X, 2023)
This paper reviews toxic plants for livestock in South America. We included 219 plants in this review, considering only the plants that caused at least one demonstrated outbreak of poisoning. Plants reported as toxic in other regions and present in South America, but with no confirmed outbreaks of poisoning in this region, are not included. We report the main aspects of the epidemiology, clinical signs, pathology and economical importance of the poisonings. Initially, the toxic plants are described based on their toxic compounds, but because the toxic compound is unknown in 92 (42%) of the plants we also classify them according to the affected system. This review highlights the great diversity of toxic plants capable of affecting livestock in South America, and for this reason studies in this regard should be intensified.